Exposure to Maternal Immune Activation Causes Congenital Unfolded Protein Response Defects and Increases the Susceptibility to Postnatal Inflammatory Stimulation in Offspring - Shimizu Y; Tsukada T; Sakata-Haga H; Sakai D; Shoji H; Saikawa Y; Hatta T (Dove Medical Press, 2021)
Yo Shimizu,1 Tsuyoshi Tsukada,2 Hiromi Sakata-Haga,2 Daisuke Sakai,3 Hiroki Shoji,3 Yutaka Saikawa,1 Toshihisa Hatta2 1Department of Pediatrics, Kanazawa Medical University, Uchinada, Ishikawa, Japan; 2Department of Anatomy, Kanazawa Medical University, Uchinada, Ishikawa, Japan; 3Department of Biology, Kanazawa Medical University, Uchinada, Ishikawa, JapanCorrespondence: Toshihisa HattaDepartment of Anatomy, Kanazawa Medical University, Uchinada, Ishikawa, JapanTel +81-76-281-8113Fax +81-76-218-8189Email thatta@kanazawa-med.ac.jpBackground: A number of childhood diseases have been identified, such as severe infection or autoinflammatory disease, in which immune overreaction against inflammation is a possible underlying mechanism. Previous reports have demonstrated that fetal cells exposed to maternal immune activation (MIA) induced by polyriboinosinic-polyribocytidylic acid [poly(I:C)] exhibited hypersensitivity to inflammation in vitro. However, the details of this mechanism remain unclear. Therefore, this study aimed to reveal the reaction to inflammation in offspring exposed to MIA in the prenatal period, as well as its molecular mechanism, using a viral infection mouse model.Materials and Methods: Pregnant mice at 12.5, 14.5, and 16.5 days post coitum were injected intraperitoneally with poly(I:C) 20 mg/kg body weight (BW) or saline. Offspring aged 3– 4 weeks received the second injection of 20 mg/kg BW or 4 mg/kg BW poly(I:C) or saline. Serum and tissues were collected at 2, 24, 48, and 72 h after the postnatal injection. The cytokine profile, histopathology of organs, and unfolded protein response (UPR) in offspring were examined.Results: The serum levels of interleukin (IL)-6, IL-17, and interferon-γ were significantly higher in the MIA group, and acute liver necrosis was detected. Moreover, failure in UPR was observed in the MIA group compared with that in the control group.Conclusion: Overall, MIA exposure in utero caused failure in UPR as well as immune overreaction to the second attack of inflammation in offspring. Our results suggested that prenatal exposure to MIA might contribute to the congenital inflammatory constitution after birth.Keywords: maternal immune activation, liver necrosis, immune overreaction, unfolded protein response defects